(untitled) (Annals of Medical Research, 2022)
Aim: Clavicle fractures mostly occur after a trauma in adults and 80% of them occur in the midshaft. Treatment is done conservatively and surgically. The aim of the study is to evaluate the effects of surgical and conservative treatments on Clavicular Shortening in terms of radiological evaluation retrospectively. Materials and Methods: The patients over the age of 18 with a midshaft clavicle fracture, who applied to our center between 2015 and 2020 and were treated conservatively and surgically, were included in the study. In both treatment groups, the clavicle lengths on the fractured side and the intact side of the patient were measured on the posterior-anterior thorax radiography, and the relevant shortness of length was determined. The rates of Clavicular Shortening and other complications occurred in both treatment groups were evaluated Results: Ages of the patients included in the study were between 18 and 71 (mean 35.6 ±12.2years) and 48 of them were treated conservatively and 28 were treated surgically. Clavicle length was determined as 158 ±11.2 mm and shortness as 8.2±9.4mm on average in the patients with a midshaft fracture, who were treated conservatively. In the patients with midshaft fracture, who were treated surgically, the length of clavicle was measured as 164±12.6mm and shortness as 3.1±5.2 mm. Statistically significant short clavicle length was determined in the patients who were treated conservatively (p<0.05). While 11 (22.9%) complications were observed in the patients treated conservatively, 9 (32.1%) complications were observed in those treated surgically. Conclusions: A lower rate of Clavicular Shortening was found in the surgical treatment of midshaft clavicle fractures. This can be one of the reasons for the increase in the tendency to surgery, as it preserves the anatomy and biomechanics of the shoulder better.